The true believer : the secret life of Noel Field, Stalin's last American spy - Marton, Kati (Simon & Schuster, 2016)
"This astonishing real-life spy thriller, filled with danger, misplaced loyalties, betrayal, treachery, and pure evil, with a plot twist worthy of John le Carre, is relevant today as a tale of fanaticism and the lengths it takes us to. True Believer reveals the life of Noel Field, an American who betrayed his country and crushed his family. Field, once a well-meaning and privileged American, spied for Stalin during the 1930s and '40s. Then a pawn in Stalin's sinister master strategy, Field was kidnapped and tortured by the KGB and forced to testify against his own Communist comrades. How does an Ivy League-educated, US State Department employee, deeply rooted in American culture and history, become a hardcore Stalinist? The 1930s, when Noel Field joined the secret underground of the International Communist Movement, were a time of national collapse: ten million Americans unemployed, rampant racism, retreat from the world just as fascism was gaining ground, and Washington--pre FDR--parched of fresh ideas. Communism promised the righting of social and political wrongs and many in Field's generation were seduced by its siren song. Few, however, went as far as Noel Field in betraying their own country. With a reporter's eye for detail, and a historian's grasp of the cataclysmic events of the twentieth century, Kati Marton captures Field's riveting quest for a life of meaning that went horribly wrong. True Believer is supported by unprecedented access to Field family correspondence, Soviet Secret Police records, and reporting on key players from Alger Hiss, CIA Director Allen Dulles, and World War II spy master, 'Wild Bill' Donovan--to the most sinister of all: Josef Stalin. A story of another time, this is a tale relevant for all times"--